Mast cell quantification in the skin of dogs with hormonal dermatosis - Costa, Glícia Meneses; Araujo, Steffi Lima; Xavier Júnior, Francisco Antônio Félix; Morais, Glayciane Bezerra de; Silveira, João Alison de Moraes; Viana, Daniel Araujo; Evangelista, Janaina Serra Azul Monteiro (Medicina Veterinária, 2020)
The mast cells are important in physiological and pathological skin events. They play an important role in the homeostatic regulatory mechanisms in the skin and thyroid gland. Mast cells present a barrier to difference external environmental stimuli and play a mediating role in the presence of infectious agents under the epidermis. This study aimed to quantify the number of mast cells in histological sections of the skin of healthy dogs and dogs with hypothyroidism and hyperadrenocorticism and to determine the distribution of mast cell numbers in the superficial dermis and deep dermis. When we compared the total mast cell count per high power field in dogs with hypothyroidism, hyperadrenocorticism and healthy dogs, only dogs with hypothyroidism had a significant difference in the quantification of mast cells per high power field, (p < 0.05). After analyzing our results, it was possible to conclude that animals with hypothyroidism produce greater amount of mast cells in the superficial dermis than patients with hyperadrenocorticism and healthy animals.